KOMPETENSI IPA TERINTEGRASI MELALUI PENDEKATAN KETERAMPILAN PROSES MAHASISWA S-1 PENDIDIKAN IPA - Insih Wilujeng, Agus Setiawan & Liliasari (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Science Education Undergraduate Students Competence in IntegratedScience through the Process Skills Approach. This study aimed to describe thecompetence of science education undergraduate students, in terms of subject mattercompetence and pedagogic competence in integrated science using the processskills approach. This study was a descriptive study involving 31 semester VI undergraduatestudents of science education. The data were collected using the integratedscience I test instrument and the integrated science II test instrument; thecompetence map development assesment instrument and integrated science learningsyllabus; and the lesson plan assessment instrument and peer teaching instrument.The results showed increases in the subject matter competence, science interdisciplinaryunderstanding competence for objective questions, and science interdisciplinaryunderstanding competence for essay questions. Students pedagogiccompetence in planning integrated science learning ranged from the good categoryto the very good category, their competence in lesson plan development was good,and their competence in doing and managing learning was fairly good.Keywords : subject matter competence, pedagogic comptetence, integrated science, process skill approach